(untitled) (American Journal of Multidisciplinary Research and Innovation, 2023)
This study determined the extent of the therapeutic communication skills of the medical and surgical nurses of the Philippine Public Hospital. This study employed a descriptive and focused research design. It utilized survey and observation methods. The researcher used a researcher-made questionnaire to describe the respondent’s profile and the extent of therapeutic communications skills, frequency counts, means, weighted means, and the rank was used. It reveals that the nurses are competent in therapeutic communication skills at the hospital regarding the Acting-Response Technique and Active Listening Response technique. It revealed that age, gender, ethnic group, the native language spoken, religion, and educational attainment were not significantly correlated to the acting response and acting listening-response techniques regarding the stand, open, lean forward, eye contact, and relax. However, the civil status of the nurse was significantly correlated to acting-response and listening techniques such as opening, paraphrasing, and reflecting. Based on this study’s significant findings, the following recommendations are drawn: Nurses should take graduate studies that will give them in-depth knowledge and practical skills in their field. They need to improve their therapeutic communication skills, develop and maintain a healing relationship in which their patient will experience security, and be optimistic that positive change is possible. Moreover, nurses should always possess a good and caring attitude toward their patients. It must be based on mutual agreement between nurses and patients as to what constitutes nurse caring behaviors. Likewise, to further enhance the therapeutic communication skills of nurses, a monthly orientation program and conducting a series of seminars must be done. Furthermore, the educational institutions offering the nursing course should emphasize their curriculum to improve the therapeutic communication skills of a student nurse.